Sleep in Children with Neuromuscular Diseases - Onofri, Alessandro; Verrillo, Elisabetta; Cutrera, Renato (Journal of Pediatric Biochemistry, 2016)
Neuromuscular diseases are a heterogeneous group of diseases affecting the nerves, muscles, anterior horn cells, or the neuromuscular junctions. They cause muscular weakness and, in most cases, involve the respiratory system, with a variable course that can lead to respiratory failure. Sleep disorders are often present in these patients, and their evaluation is necessary to assess the requirements for correct management. Hypoventilation, obstructive sleep apnea, and central apneas must be assessed and eventually treated with mechanical ventilatory support. Polysomnography with capnography is the gold standard in assessing sleep-disordered breathing. This review aims to provide an overview of the literature on the most common neuromuscular diseases with related sleep breathing disorders in children, highlighting the main features of sleep in these patients and the role of noninvasive ventilation in treating these conditions.
Keywords: neuromuscular diseases; sleep-disordered breathing; polysomnography; sleep related hypoventilation; obstructive sleep apnea; noninvasive ventilation